As atitudes de estudantes do ensino médio em relação à disciplina de matemática em escolas do município de Viamão - Silva, Vagner Jorge da (2011)
Mathematics becomes disciplinary, depending on how it is crafted by the educator. This is because it is the most responsible for producing failures in weight for elementary and high school. This work deals with the student's behavior can be directly linked to what is presented to them in the classroom. It reflects on the actions coming from reactions to stimuli that the educators create through their methodologies. Recognizing that these actions depend on how the teacher acts in the classroom, theorists have proposed a more individualized observation about evaluation, exercise and appreciation of mathematics in the interpersonal relationships between teacher and student. The importance of the theoretical contributions of Pedro Demo, this research is to encourage the educator to a constant reconstruction of its shares heading to the achievement of predetermined goals for lesson planning and school. As active subjects in the process of cognitive development of autonomy that research shows that students should realize their responsibility in the learning process. In order to identify and describe the attitudes of students and their conceptions, this study applied two questionnaires to 150 high school students from three schools Viamão, one private and two public.A questionnaire of open character and purpose, organized so that students were pragmatic in their responses and the other with ten objective questions, attitude scale with four points. The interviews were conducted with ten students in order to relate concepts to activities that have front Mathematics. The research started from a quantitative view, from which it was addressed qualitative analysis of material from questionnaires and interviews, using the Discourse Textual Analysis. The research enabled the realization that the attitudes of students who have the motivation depending on the class. We were able to realize that good planning is essential in class and a recognition of the context in which students are included, however students can not perceive a relationship of course with the environment in which they live. The actions that students perform is what produces an environment conducive to their growth in cognitive development of autonomy in mathematics activities proposed. This work thus seeks to identify, correlate and analyze the attitudes and concepts that the students in the third year of high school have in relation to mathematics, verifying that the manifestations of these attitudes.